Relações intergovernamentais na implementação de políticas públicas: o caso do SAMU no Estado do Paraná - Marroni, Carlos Henrique (2017)
This research is devoted to the discussion about federation forums in the SUS and territorial associations (intermunicipal public consortia) in intergovernmental relations in the implementation of public policies. The thesis is based on the literature on federalism, intergovernmental relations, decentralization and federative coordination to build a theoretical reference that analyzes the intergovernmental relations in the implementation of emergency public policy with federative coordination, in particular in the relationship between the subnational state, Paraná and the municipalities, considering the federative forums such as the Bipartisan Commission of the SUS - CIB and the intermunicipal consortium (territorial associativism). The purpose of this study is to identify and analyze the role of federative forums of negotiation in SUS, as well as the influence of the tradition of territorial associativism present in the State of Paraná, in the configuration of the pattern of intergovernmental relations existing in the implementation of SAMU in the State of Paraná. The study of two cases of implementation of prehospital mobile care (SAMU 192) in the State of Paraná, Cascavel and Maringá, was carried out in three research stages: a) bibliographical; B) documentary; and c) field research. As a result, it can be stated that the Unified Health System (SUS) pacts provided wide negotiations between federal, state and municipal entities, setting up a pattern of intergovernmental relations of coordinated authority, as well as intermunicipal consortium Participation of smaller and poorer municipalities in the negotiation.